2020
DOI: 10.1002/ccd.29066
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of patent and occlusive hemostasis after transradial coronary procedures

Abstract: Objectives To assess the independent predictors of patent and occlusive hemostasis (PH and OH, respectively) during radial hemostasis after coronary procedures. Background Radial artery occlusion (RAO) is a thrombotic complication of transradial catheterization that can lead to permanent occlusion of the radial artery. Sheath‐vessel diameter ratio, postprocedure compression time, occlusive hemostasis, inadequate, and excessive anticoagulation are all predictors of RAO. Methods As a part of a previously publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…. Recently in a prospective, multicenter, ob-servational cohort registry, Pacchioni et al(44) reported a U-shaped relationship with activated clotting time value and RAO in 837 patients who underwent transradial coronary diagnostic angiography or interventions. The paradoxical rise in rates of RAO at increasing ACT was explained by mitigation of the protective effect of high anticoagulation level because of longer hemostasis time, more frequent occlusive hemostasis, and decrease in rate of successful patent hemostasis.…”
mentioning
confidence: 99%
“…. Recently in a prospective, multicenter, ob-servational cohort registry, Pacchioni et al(44) reported a U-shaped relationship with activated clotting time value and RAO in 837 patients who underwent transradial coronary diagnostic angiography or interventions. The paradoxical rise in rates of RAO at increasing ACT was explained by mitigation of the protective effect of high anticoagulation level because of longer hemostasis time, more frequent occlusive hemostasis, and decrease in rate of successful patent hemostasis.…”
mentioning
confidence: 99%
“…Certainly, PH and minimal inflation protocols depend on different factors, and among them level of anticoagulation and introducer sheath diameter play a pivotal role. 22 Even after adjustment for these confounders, PH rate and consequent effective PF rate was still lower in TRA group, thus confirming the advantages of DRA.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, in these anatomies, that are not infrequent, 21 distal and conventional puncture potentially differs only for hemostasis protocol and hemostasis time. Certainly, PH and minimal inflation protocols depend on different factors, and among them level of anticoagulation and introducer sheath diameter play a pivotal role 22 . Even after adjustment for these confounders, PH rate and consequent effective PF rate was still lower in TRA group, thus confirming the advantages of DRA.…”
Section: Discussionmentioning
confidence: 81%
“…Ainda no que se comparam os dois métodos de hemostasia, mesmo que de baixa incidência, a OAR que acomete de 1 a 10% e é também uma das complicações relacionadas ao procedimento, é maior constatada na utilização do método compressivo convencional em relação ao uso da pulseira hemostática (Santos, et al, 2018). Estudos apontam, também, que o nível de anticoagulação e a utilização de introdutor com calibre inadequado, está fortemente relacionado à incidência de OAR, devendo assim, ser realizado uma avaliação prévia do paciente com relação aos fatores de coagulação e seu diâmetro arterial para a seleção adequada do introdutor (Pacchioni, et al, 2021;Lavi, et al, 2020).…”
Section: Discussionunclassified